2018
DOI: 10.3389/fpubh.2018.00006
|View full text |Cite
|
Sign up to set email alerts
|

The CARPEDIEM Algorithm: A Rule-Based System for Identifying Heart Failure Phenotype with a Precision Public Health Approach

Abstract: Modern medicine remains dependent on the accurate evaluation of a patient’s health state, recognizing that disease is a process that evolves over time and interacts with many factors unique to that patient. The CARPEDIEM project represents a concrete attempt to address these issues by developing reproducible algorithms to support the accuracy in detection of complex diseases. This study aims to establish and validate the CARPEDIEM approach and algorithm for identifying those patients presenting with or at risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
0
11
1
Order By: Relevance
“…Although further study is needed, a frequent program might be effective to promote the habit of exercise without discontinuation or dropouts. Because organizational culture or support (e.g., management or leadership for health promotion, enhancing coworkers’ communication, setting an organization’s mission statement or policies) could be essential elements for successful workplace intervention (Taylor et al, 2018), enhancing these factors is important when implementing such programs.…”
Section: Discussionmentioning
confidence: 99%
“…Although further study is needed, a frequent program might be effective to promote the habit of exercise without discontinuation or dropouts. Because organizational culture or support (e.g., management or leadership for health promotion, enhancing coworkers’ communication, setting an organization’s mission statement or policies) could be essential elements for successful workplace intervention (Taylor et al, 2018), enhancing these factors is important when implementing such programs.…”
Section: Discussionmentioning
confidence: 99%
“…The adoption of patient portals to disclose test history in youth populations can be understood through constructs of behavior theory [ 20 ]. Latent constructs are measures of “behaviors, attitudes, and hypothetical scenarios we expect to exist as a result of our theoretical understanding of the world”, assessed using an instrument consisting of survey items or psychometrics [ 21 , 22 ]. Performance expectancy is a construct of technology adoption theory referring to the degree to which the technology provides benefits or relative advantages to executing a task or set of tasks [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Latent constructs are measures of “behaviors, attitudes, and hypothetical scenarios we expect to exist as a result of our theoretical understanding of the world”, assessed using an instrument consisting of survey items or psychometrics [ 21 , 22 ]. Performance expectancy is a construct of technology adoption theory referring to the degree to which the technology provides benefits or relative advantages to executing a task or set of tasks [ 22 , 23 ]. It may be hypothesized that performance expectancies about the interpersonal use of patient portals to disclose STI test history are key determinants of behavioral intentions within populations of Black youth.…”
Section: Introductionmentioning
confidence: 99%
“…As children and youth spend a significant amount of their day at school, school-based health promotion programs offer another favorable strategy to improve health and wellness [ 1 ]. A recent systematic review found that Indigenous youth peer-led health promotion programming in Australia, Canada, New Zealand, and the United States led to improved health-related knowledge, attitudes, and behaviors [ 13 ]. The review included 20 interventions, seven of which were school-based, with many using cultural and artistic activities (e.g., dance, music, performances) as a means of engaging youth.…”
Section: Introductionmentioning
confidence: 99%